Efeitos da melatonina durante o cultivo in vitro de folículos pré-antrais e antrais e na maturação in vitro de complexos cumulus-oócito bovinos - Silva, Bianca Régia (2023)
The objectives of the present study were: 1) Investigate the effects of melatonin alone or in association with the antagonist luzindole or the mTORC1 inhibitor rapamycin on bovine ovarian tissue cultured in vitro (Phase 1); 2) Evaluate the effects of different concentrations of melatonin during the in vitro culture of bovine early antral follicles (Phase 2) and 3) Investigate the effects of modulation of cyclic adenosine monophosphate during in vitro prematuration and the role of melatonin in vitro maturation (MIV) of bovine CCOs (Phase 3). In phase 1, fragments of ovarian tissue were cultured for six days in α-MEM+ alone or supplemented with melatonin (1000 pM), melatonin and luzindole (1000 pM) or melatonin and rapamycin (0.16 µg/ml). In phase 2, isolated early antral follicles were cultured in TCM-199+ alone or supplemented with 10-6, 10-7, or 10-8 M melatonin at 38.5°C with 5% CO2 for 8 days. After culture, follicular growth, ultrastructure, chromatin configuration, viability and ROS and mRNA levels were investigated. Phase 3 included two experiments. In experiment 1, CCOs were pre-matured for 8 h in control medium or with 3-isobutyl-1-methylxanthine (IBMX) and forskolin, IBMX and C-type natriuretic peptide (CNP), CNP and forskolin or IBMX, CNP and forskolin. In experiment 2, CCOs were pre-matured, followed by IVM in control medium alone or with 10-6, 10-7 or 10-8 M melatonin. After IVM, chromatin configuration, transzonal projections (TZPs), reactive oxygen species, mitochondrial distribution, ultrastructure and mRNA expression were evaluated. To verify data normalization, the Shapiro-Wilk test was used. The mRNA levels were analyzed using the Kruskal-Wallis test and for other assessments, in general, the ANOVA and Tukey tests were used. In phase 1, ovarian tissues cultured with melatonin, melatonin and luzindole or melatonin and rapamycin showed a significantly higher percentage of morphologically normal follicles compared to the control medium. Melatonin reduced the percentage of primordial follicles, increased the percentage of developing follicles and collagen levels. However, these effects were blocked by luzindole or rapamycin (P<0.05). In phase 2, early antral follicles cultured with 10-6 M and 10-8 M melatonin had a progressive increase in their diameters during the culture period (P < 0.05). Furthermore, oocytes from follicles cultured with 10-7 or 10-8 M melatonin showed increased fluorescence for calcein-AM. Follicles cultured with 10-8 M melatonin showed well-preserved ultrastructure. In phase 3, higher rates of meiotic resumption were observed in the 10-8 M melatonin treatment (P<0.05). CCOs matured with 10-7 or 10-8 M melatonin showed greater mitochondrial activity (P<0.05), while those matured with 10-6 or 10-8 M showed higher levels of TZPs. CCOs matured with 10-8 M melatonin increased mRNA expression for superoxide dismutase (SOD) and catalase (CAT) (P<0.05), when compared to uncultured and pre-matured CCOs, respectively. In conclusion, melatonin supplementation during bovine ovarian tissue culture promotes follicular activation and increases collagen fibers through its membrane-coupled receptors and mTORC1. Furthermore, supplementation of 10-8 M melatonin in the culture of early antral follicles improves oocyte viability and preserves the ultrastructure of the organelles in oocyte and granulosa cell membranes. Finally, prematuration with CNP and forskolin combined with supplementation of 10-8 M melatonin during IVM, improves meiotic resumption rates, preserves TZPs, increases mitochondrial activity and relative mRNA expression for SOD and CAT in CCOs.